Wymowa sceniczna w śpiewie - Nabiałek, Małgorzata (Investigationes Linguisticae, 2012)
This article is to explain why listeners often find it hard to understand the opera singing, and to emphasize the importance of singers’ and conductors’ awareness of diction in singing. The author defines the term “diction in classical singing”, what exactly the subject of this discipline is and what problems and difficulties may both singers and diction coaches encounter in the process of preparing the textual layer of a musical piece.